1993
DOI: 10.1002/hc.520040407
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylated indolizines

Abstract: Preparative methods o f synthesis of 1and 3-phosphino-indolizines by interaction between 2-substituted indolizines with phosphorus(III) halogenides in the presence of bases have been developed. I t was found that originally this reaction results in the formationof 1 -phosphino-indolizines which then undergo izommiation into 3-phosphino isomevs. One, two, or three indolizine substituents can be consecutively attached to the phosphorus atom. New methods of syntheses of 1,3-diphosphino-indolizines have been devel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
1

Year Published

1996
1996
2009
2009

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 4 publications
2
12
1
Order By: Relevance
“…As regards isomerizations in indolizine molecules, dichlorophosphino, dibromophosphino, and diphenylphosphino groups have been shown to migrate [5]. In the case of N-methylpyrrole, we failed to extend the 2 → 3 isomerization found to other phosphorus-containing groups.…”
Section: Resultscontrasting
confidence: 45%
“…As regards isomerizations in indolizine molecules, dichlorophosphino, dibromophosphino, and diphenylphosphino groups have been shown to migrate [5]. In the case of N-methylpyrrole, we failed to extend the 2 → 3 isomerization found to other phosphorus-containing groups.…”
Section: Resultscontrasting
confidence: 45%
“…As previously reported, 1,3-azoles can be directly C-phosphorylated with phosphorus(III) halides in pyridine in the presence of Et 3 N [13]. Under such conditions, 1-alkylimidazoles readily react with PHal 3 to give 2-phosphorylated products [14], whereas 1-aryl-2-methylimidazoles undergo phosphorylation at the methyl group [15].…”
Section: Introductionmentioning
confidence: 84%
“…By NMR spectroscopy and analysis of literature data [11], we have shown that the electrophilic attack on indolizines 7a,b by the Kirsanov isocyanate occurs at position 3 of the heterocycle, as is the case with carbonyl chlorides [12] and haloid derivatives of P(III) acids [11].…”
Section: Resultsmentioning
confidence: 99%
“…After having been washed with acetonitrile (3 mL), the product was dried. 1 (11). Compound 11 was prepared analogously to compound (3b) in benzene.…”
Section: 5-dimethyl-1-(4-iodophenylmentioning
confidence: 99%